POLLUTION OF THE FOREST AND AGRICULTURAL SOILS WITH HEAVY METALS - Ramona Violeta Cazalbaşu (Analele Universităţii "Constantin Brâncuşi" din Târgu Jiu: Seria Inginerie, 2018)
Biotope composed of ground, geographical and climatic factors, and in direct relationship with plants and animals, constitute the terrestrial, within which, by its functions, soil is a matter of importance. If only the ecological functions, soil fertility, the role of the filter and the function of the genetic reserve, can appreciate the role of the ground in growth and development of the plants, in the prevention of soil disturbance trophic chain--plants and animals-man in ensuring the conditions necessary for the existence of biodiversity dim edafic environment. If, on these eco-features, add and economical, even if they sometimes appear contradictions, arriving at the actual size of the importance of the role of the ground as the main resource of agricultural production, forestry and food for humanity. For these reasons the ground must use reasonable, protected against pollution which produces pertubari at the level of its functions, with serious consequences in the long term.